Structuring and coding in health care records: a qualitative analysis using diabetes as a case study. Issue 2 (1st April 2015) - Robertson, Ann R R; Fernando, Bernard; Morrison, Zoe; Kalra, Dipak; Sheikh, Aziz
Abstract : Background: Globally, diabetes mellitus presents a substantial and increasing burden to individuals, health care systems and society. Structuring and coding of information in the electronic health record underpin attempts to improve sharing and searching for information. Digital records for those with long-term conditions are expected to bring direct and secondary uses benefits, and potentially to support patient self-management. Aims and objectives: We sought to investigate if how and why records for adults with diabetes were structured and coded and to explore a range of UK stakeholders' perceptions of current practice in the National Health Service. Methods: We carried out a qualitative, theoretically informed case study of documenting health care information for diabetes in family practice and hospital settings in England, using semi-structured interviews, observations, systems demonstrations and documentary data. Results: We conducted 22 interviews and four on-site observations. With respect to secondary uses – research, audit, public health and service planning – interviewees clearly articulated the benefits of highly structured and coded diabetes data and it was believed that benefits would expand through linkage to other datasets. Direct, more marginal, clinical benefits in terms of managing and monitoring diabetes and perhaps encouraging patient self-management were also reported. We observed marked differences in levels of record structuring and/or coding between family practices, where it was high, and the hospital. We found little evidence that structured and coded data were being exploited to improve information sharing between care settings. Conclusions: Using high levels of data structuring and coding in records for diabetes patients has the potential to be exploited more fully, and lessons might be learned from successful developments elsewhere in the UK. A first step would be for hospitals to attain levels of health information technology infrastructure and systems use commensurate with family practices.